Le face à face hirak-pouvoir : La crise de la représentation - Louisa Dris Aït-Hamadouche; Chérif Dris (L’Année du Maghreb)
Since the popular uprising of 22 February, the question of the representativity of the Algerian hirak has been haunting. How could a mass movement of this magnitude, with all its spatial, human and even temporal variations, have been able to unfold in a peaceful and lasting way, in spite of the periods when the mobilization had ebb? How could a movement for which no political, trade union or social force could claim paternity have forced a President of the Republic to give up a fifth term and continue in the long term while radicalizing his claims?Faced with an unprecedented situation where popular protest and lack of mediation mingle, what answers did the governors provide? To answer this series of questions, we propose to examine the hypothesis according to which the attachment of the holders of the power to the return to a controlled electoral process pushes them to look for resource actors within the contest. A choice facilitated by a partisan opposition unable to turn into a mediator.